Evaluating the Implementation of an Early Palliative Care Screening Tool for Inpatients at Persahabatan Hospital: Impact on Quality of Care, Length of Stay, and Clinical Outcomes - Khonsa, Oni; Meliala, Andreasta; Darwito, Darwito (Indonesian Journal of Cancer, 2025)
Background: Palliative care is integrated medical care that is active and comprehensive, with a multidisciplinary approach to reduce the pain of terminally ill patients at the end of their lives. Persahabatan Hospital, as a national referral Type A hospital, receives many patients in severe and complex conditions, some of whom require palliative care. Early identification of Palliative Care Screening Tool (PCST) screening can result in more effective interventions and more optimal care in improving quality of life, reducing length of stay, and intensive care unit (ICU) admission rates. This study aims to assess the early implementation outcomes of the PCST in inpatients at Persahabatan Hospital. Method: This research is a sequential explanatory mixed methods design that examines how the implementation evaluation of PCST in palliative care at Persahabatan General Hospital is conducted, utilizing both retrospective quantitative and qualitative approaches. The quantitative approach involves utilizing secondary data from medical records and the PCST at Persahabatan General Hospital in Jakarta from January to December 2023. A random sampling technique was applied to select patients diagnosed with palliative care conditions, including severe liver disease,end-stage kidney disease, chronic obstructive pulmonary disease (COPD), advanced heart failure,and other chronic illnesses. At the same time, the qualitative approach employs the focus group discussion analysis method.Results: Out of 82 patients who underwent PCST screening, 56 patients underwent early screening, and 26 patients underwent late screening. The median length of stay for patients with early screening was 4 days, whereas for those with late screening, it was 18 days (p 0.001). Early screening had a relative risk of 4.34 (1.72–26.2) for successful palliative screening compared to late screening. Based on the analysis of the focus group discussion results, the main issues in implementing early screening were a lack of understanding of the screening process and difficulties in its implementation